Preparation method of coal-based porous graphene composite ternary material
By using low-cost coal in hybrid capacitors to prepare coal-based porous graphene materials and composite them with ternary materials, the preparation of high-specific energy mixed capacitance positive electrode materials is achieved, and the problems of insufficient energy density of coal-based porous graphene positive electrode materials and poor positive electrode ratio performance of ternary materials are solved, and it has broad application prospects and significant economic value.
Patent Information
- Application Number
- CN202411685631.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-23
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-23
AI Technical Summary
The coal-based porous graphene cathode material has insufficient energy density, which limits its performance in actual applications. At the same time, although the ternary cathode has a high specific capacity, its rate performance is poor, its cost is high, and its cycle life is short.
Coal-based porous graphene materials are prepared by using low-cost coal as porous carbon precursor, carbonization and then activation, and composited with ternary materials. The surface adsorption ion storage mechanism of coal-based porous graphene and the bulk phase embedded ion storage mechanism of ternary materials are used to achieve body surface synergistic effects between materials.
The high-specific energy hybrid capacitor positive electrode composite material has been prepared, which has broadened the application field of coal and improved the performance of energy storage materials, and provided new ideas for the development of energy storage technologies such as hybrid capacitors. It has broad application prospects and significant economic value.
Smart Images

Figure CN119637858A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a coal-based porous graphene composite ternary material, and belongs to the technical field of material preparation. Background Art
[0002] In order to solve the problem of low energy density of supercapacitors, Faraday electrodes (battery-type electrodes) are introduced into supercapacitors to form hybrid capacitors (such as lithium / sodium / potassium hybrid capacitors), which moderately sacrifice power density and cycle life to improve the energy density of the device. The positive electrode material of the hybrid capacitor is a capacitive material, and its energy storage mechanism is the rapid adsorption / desorption process of ions on the electrode material / electrolyte interface, so it has a higher power density and a longer cycle life; the negative electrode material is a battery-type material, and its energy storage mechanism is the embedding / de-embedding process of ions in the electrode material, so it has a higher energy density. Hybrid capacitors have the characteristics of greatly improving energy density without sacrificing power density, and have a cycle life far exceeding that of lithium batteries. At present, the energy density of hybrid capacitors is about 10-50Wh / kg, the power density is ≥10kW / kg, the cycle life can reach 50,000-100,000 times, and the working life can reach 10 years.
[0003] Electrode materials are a key part that affects the energy storage performance of hybrid capacitor systems. How to prepare highly active and highly stable electrode materials is an important development direction for supercapacitors. Ideal positive electrode materials should have high conductivity, good mechanical properties, stable chemical properties, and high specific surface area. Among the positive electrode materials of hybrid capacitors, materials such as activated carbon, metal oxides, and conductive polymers are widely used due to their unique electrochemical properties. However, these materials still have room for improvement in specific energy and specific power, so the development of new high-performance electrode materials has become the focus of current research.
[0004] Porous carbon materials belong to the category of nanomaterials. They are network-structured materials composed of interconnected or closed pores, with adjustable pores and structures. By regulating the pore distribution characteristics of porous materials to give them high specific surface area and pore volume, the ion diffusion channels can be expanded; at the same time, by regulating the microcrystalline structure of the material to fully develop it, the conductivity and chemical structure stability of the material can also be improved. Based on the structure-activity relationship between the microcrystalline development and pore structure of porous carbon and application performance, constructing porous carbon with high specific surface area and high-quality graphite microcrystals is an important goal for preparing high-performance electrode functional materials.
[0005] Low-cost preparation methods and the selection of precursors (carbon-based materials) are the key to determining the morphology, properties and application performance of porous carbon materials. Based on existing technical means, porous carbon is generally prepared by template method, physical activation method and chemical activation method internationally. The template method uses the method of depositing porous carbon precursors into the pores or surface of the template, removing the template after deposition, and obtaining porous nanomaterials with the same morphology and size as the template. However, this method requires that the carbon-based material has good fluidity before it can be evenly mixed with the template. For solid precursors, a complex pretreatment process is required, which is costly, and there is a lack of regulation of the microcrystalline structure in the process of preparing porous carbon by the template method, and the microcrystalline structure of carbon is usually difficult to fully develop. The physical activation process is mainly manifested as the oxidative etching of weak oxidizing gases (such as carbon dioxide, water vapor, etc.) on carbon-based materials. The process is affected by gas adsorption, oxidative etching and product diffusion rate. The porous carbon materials obtained by physical activation are mainly micropores with a narrow pore size distribution. Chemical activation is the development of pores through the chemical reaction of chemical reagents and precursors. Compared with physical activation, chemical activation shows higher carbon yield and specific surface area. The activation mechanism of general chemical activators (such as protonic acids, etc.) is mainly to promote the catalytic dehydration of the hydrogen and oxygen functional groups of coal-based materials. The pore-forming process is relatively mild and cannot achieve developed pores. Potassium-based activators (such as potassium hydroxide, potassium ferrate, etc.) achieve pore formation through their strong corrosiveness and oxidation at high temperatures. At the same time, the intermediate products in the activation process (such as potassium element) will catalyze the graphitization process of carbon materials, and at the same time intercalate into the interlayers of graphite microcrystals, further generating pores and increasing the specific surface area.
[0006] Biomass and coal are natural treasure troves of solid carbon resources with high carbon density, and can be used as precursors to prepare porous carbon materials. However, carbon materials with different structures also have great differences in internal pores, surface chemical properties and mechanical properties. The carbon structure in biomass contains a large number of oxygen-containing groups (hydroxyl, carboxyl, carbonyl, ether bonds, etc.), long aliphatic side chains, and heterocyclic cross-linked (semi)cellulose or lignin structures, and the degree of aromatic polymerization is low. Due to the diversity of biomass sources, its microstructure exhibits a variety of irregular structures such as spherical, fibrous, lamellar, tubular and rod-shaped. By activating the biomass carbon source and removing the rich organic and volatile components in the carbon source, a carbon material with a certain pore size structure is obtained. However, in the process of preparing developed pores, a certain degree of pyrolysis and polycondensation reactions occur inside the structure, generating a large number of unpaired electrons, forming five-membered and seven-membered heterocyclic rings, resulting in a certain degree of distortion and deformation of the structural lamellae, which in turn leads to poor structural stability of biomass-based porous carbon, which cannot meet the high stability requirements of supercapacitor electrode materials.
[0007] As the most important primary energy source in my country, coal has abundant reserves and low cost, which provides the necessary conditions for the large-scale production of porous carbon. Compared with biomass, the microcrystalline structure of coal is relatively dense, which is an ordered macromolecular structure formed by plant dehydrogenation, deoxygenation, and aromatization polymerization. It brings more possibilities for the preparation of porous carbon using coal as a carbon material precursor and the coordinated regulation of its microcrystalline structure and pore structure development. 3 Carbon is the main connecting structure of graphite microcrystals and is also a structure that is more likely to react with activators. By first carbonizing coal, the crystal structure is arranged more regularly, and the microcrystals are larger in size and have higher structural stability. Then chemical activation can achieve deep coordinated regulation of pores and graphite microcrystals to obtain coal-based porous graphene materials.
[0008] Coal-based porous graphene cathode materials show great application potential in the field of hybrid capacitors due to their high specific surface area and good electrical conductivity. At present, the preparation methods of coal-based porous graphene cathodes mainly include carbonization and activation reactions. Through high-temperature carbonization and activation processes, the carbon source material is converted into a graphitized porous carbon structure, which is then crushed and sieved to obtain a porous carbon powder of the desired particle size. Finally, the electrochemical properties of the porous carbon material are improved by surface treatment. However, due to the limitation of the surface storage mechanism of ions, although coal-based porous graphene cathode materials can achieve fast charging and discharging, they still have shortcomings in energy density, which limits their performance in practical applications.
[0009] Ternary materials, such as lithium nickel cobalt manganese oxide (LiNi x Co y Mn 1-x-y O2), due to its high specific capacity and stable cycle performance, it has become one of the preferred positive electrode materials for lithium-ion batteries and hybrid capacitors. The preparation methods of ternary materials mainly include solid phase method, coprecipitation method, sol-gel method and template method. Although ternary materials have the advantages of high energy density, their cycle life is relatively short, the cost is high, and the performance decays rapidly under high temperature environment. Especially as the positive electrode material of hybrid capacitors, the bulk ion storage process limits its rate performance.
[0010] In summary, coal-based porous graphene cathode materials are difficult to meet the demand for high energy density, and although the ternary material cathode has a high specific capacity, its rate performance is poor, the cost is high, and the cycle life is short. Therefore, a new type of coal-based porous graphene composite ternary material is developed as a hybrid capacitor cathode material to overcome the shortcomings of the coal-based porous graphene cathode and the ternary material cathode. The preparation method of high specific energy hybrid capacitor cathode based on coal-based porous graphene composite ternary material aims to make full use of the surface adsorption ion storage mechanism of coal-based porous graphene and the bulk embedded ion storage mechanism of ternary materials through the composite of coal-based porous graphene and ternary materials, so as to achieve the bulk synergistic effect between materials, thereby preparing a high specific energy hybrid capacitor cathode composite material. This preparation method is expected to provide new ideas and technical support for the research and development of hybrid capacitor electrode materials, and promote the development and application of hybrid capacitor technology. Summary of the invention
[0011] In order to solve the problems existing in the background technology, the present invention provides a method for preparing a coal-based porous graphene composite ternary material.
[0012] To achieve the above object, the present invention adopts the following technical scheme: a method for preparing a coal-based porous graphene composite ternary material, the method comprising the following steps:
[0013] S1: Raw material refinement: The coal raw material is crushed, ground and screened in sequence to obtain refined coal powder; the particle size of the refined coal powder is 60 mesh to 200 mesh.
[0014] S2: Carbonization of coal raw materials: The refined coal powder is placed in an atmosphere furnace, the temperature is raised to a specified carbonization temperature and kept warm for a period of time, and then the atmosphere furnace is naturally cooled to room temperature to obtain a carbonized solid material;
[0015] S3: Mixing of activator and product: Fully and uniformly mix the carbonized solid material and the chemical activator in a mass ratio of 1:0.1-10 to obtain a mixture; the chemical activator is one or more potassium-based activators.
[0016] S4: Activation of the mixture: the mixture is transferred to a crucible and placed in an atmosphere furnace, the temperature is raised to a specified activation temperature and kept warm for a period of time, and then the atmosphere furnace is naturally cooled to room temperature to obtain an activated mixed solid material;
[0017] S5: cleaning and drying of the activated product: the activated mixed solid material is sequentially acid-washed and water-washed until the supernatant is neutral, and then the cleaned solid material is dried to obtain a coal-based porous graphene material;
[0018] S6: Mixing of ternary metal salts: nickel salt, cobalt salt and manganese salt are mixed in any proportion to obtain a mixture; the nickel salt, cobalt salt and manganese salt are corresponding sulfates, carbonates, chlorides, fluorides or hydroxides. The mixing method is coprecipitation, liquid phase mixing or solid phase mixing.
[0019] S7: Mixing the mixture with a lithium source: Mixing the mixture with a lithium source to obtain a precursor material; the lithium source is lithium carbonate, lithium hydroxide, lithium nitrate or lithium chloride. The mixing method is liquid phase mixing or solid phase mixing.
[0020] S8: sintering of precursor materials: placing the precursor materials in an atmosphere furnace, raising the temperature to a specified temperature and keeping the temperature for a period of time, then naturally cooling the atmosphere furnace to room temperature to obtain a sintered mixed solid material;
[0021] S9: cleaning and drying of the product: the mixed solid material after sintering is sequentially acid-washed and water-washed until the supernatant is neutral, and the cleaned solid material is dried to obtain a ternary material;
[0022] The pickling solutions used in the pickling treatments of S5 and S9 are all dilute hydrochloric acid, dilute nitric acid or dilute acetic acid, and the concentrations of the pickling solutions are all 0.01 mol / L to 10 mol / L.
[0023] S10: Preparation of composite materials: Mixing the coal-based porous graphene material and the ternary material in a mass ratio of 1:100 to 100:1 to obtain a coal-based porous graphene composite ternary material.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The present invention uses low-cost coal as a porous carbon precursor, and effectively prepares coal-based porous graphene materials by a method of carbonization followed by activation, which is suitable for mass production; a potassium-based activator is used to simplify the process, while catalyzing the graphitization process and promoting the coordinated development of pores and graphite microcrystalline structures; coal-based porous graphene is composited with ternary materials, and a high-specific-energy hybrid capacitor positive electrode composite material is prepared based on the surface synergistic energy storage mechanism. The present invention not only broadens the application field of coal, but also improves the performance of energy storage materials, provides new ideas for the development of energy storage technologies such as hybrid capacitors, and has broad application prospects and significant economic value. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is a SEM image of the coal-based porous graphene composite ternary material prepared in Example 1 of the present invention;
[0027] Figure 2 This is a Raman spectrum of the coal-based porous graphene composite ternary material prepared in Example 1 of the present invention;
[0028] Figure 3 1 is an electrochemical characteristic diagram of the coal-based porous graphene composite ternary material prepared in Example 1 of the present invention, wherein: (a) is a cyclic voltammetry curve of a coal-based porous graphene-based supercapacitor; (b) is a constant current charge-discharge curve of a coal-based porous graphene-based supercapacitor;
[0029] Figure 4 is a SEM image of the coal-based porous graphene composite ternary material prepared in Example 2 of the present invention;
[0030] Figure 5 This is a Raman spectrum of the coal-based porous graphene composite ternary material prepared in Example 2 of the present invention;
[0031] Figure 6 1 is an electrochemical characteristic diagram of the coal-based porous graphene composite ternary material prepared in Example 2 of the present invention, wherein: (a) is a cyclic voltammetry curve diagram of the coal-based porous graphene-based supercapacitor; (b) is a GCD curve diagram of the coal-based porous graphene-based supercapacitor;
[0032] Figure 7 is a SEM image of the coal-based porous graphene composite ternary material prepared in Example 3 of the present invention;
[0033] Figure 8 This is a TEM image of the coal-based porous graphene composite ternary material prepared in Example 3 of the present invention;
[0034] Fig. 9 The graphs are a comparison of the nitrogen adsorption curve and pore size distribution curve of the coal-based porous graphene composite ternary material prepared in Examples 1-3 of the present invention, wherein: (a) is a nitrogen adsorption / desorption isotherm graph; (b) is a pore size distribution curve graph;
[0035] Fig.10 1 is an electrochemical characteristic diagram of an organic supercapacitor of a coal-based porous graphene composite ternary material prepared in Example 3 of the present invention, wherein: (a) is a cyclic voltammetry curve of a coal-based porous graphene-based supercapacitor; (b) is a constant current charge-discharge curve of a coal-based porous graphene-based supercapacitor;
[0036] Fig.11 The cyclic voltammetry curve and constant current charge-discharge curve of a lithium ion capacitor with the coal-based porous graphene composite ternary material as the positive electrode and the niobium-based oxide as the negative electrode prepared in Example 3 of the present invention, wherein: (a) is a cyclic voltammetry curve; (b) is a constant current charge-discharge curve. DETAILED DESCRIPTION
[0037] The technical solution of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0038] A method for preparing a coal-based porous graphene composite ternary material, the method comprising the following steps:
[0039] S1: Raw material refinement: The coal raw material is crushed, ground and screened in sequence to obtain refined coal powder; the particle size of the refined coal powder is 60 mesh to 200 mesh.
[0040] The coal raw material is low-cost coal without any pretreatment, and its industrial analysis shows that the moisture content is 0-15%, the ash content is 0-5%, the volatile matter content is 0-40%, and the fixed carbon content is more than 50%; the element analysis shows that the carbon content is more than 70%, the hydrogen content is 0%-10%, and the oxygen content is 0%-20%.
[0041] S2: Carbonization of coal raw material: Place the refined coal powder in an atmosphere furnace (the atmosphere of the atmosphere furnace is high-purity nitrogen or high-purity argon, and the volume flow rate of the atmosphere is 50mL / min to 500mL / min. The heating rate of the atmosphere furnace is 0.1℃ / min to 20℃ / min), the temperature is raised to the specified carbonization temperature (600℃ to 1200℃) and kept warm for a period of time (0.5h to 10h), and then the atmosphere furnace is naturally cooled to room temperature to obtain a carbonized solid substance;
[0042] S3: Mixing of activator and product: The carbonized solid material and the chemical activator are fully and evenly mixed in a mass ratio of 1:0.1 to 10, and the mixing method is ball milling or liquid phase mixing to obtain a mixture; the chemical activator is one or more of potassium-based activators (such as potassium hydroxide, potassium carbonate, potassium bicarbonate, potassium ferrate, etc.).
[0043] S4: Activation of the mixture: The mixture is transferred to a crucible and placed in an atmosphere furnace (the atmosphere of the atmosphere furnace is high-purity nitrogen or high-purity argon, and the volume flow rate of the atmosphere is 50 mL / min to 500 mL / min. The heating rate of the atmosphere furnace is 0.1°C / min to 20°C / min), the temperature is raised to a specified activation temperature (600°C to 1200°C) and kept warm for a period of time (0.5h to 10h), and then the atmosphere furnace is naturally cooled to room temperature to obtain an activated mixed solid material;
[0044] S5: Cleaning and drying of the activated product: The activated mixed solid material is acid-washed and water-washed in turn, and the cleaning method is vacuum filtration or solid-liquid separation by centrifuge. After the supernatant is neutral, the cleaned solid material is dried, and the drying method is vacuum drying, hot air drying or natural evaporation. The drying temperature is 60-160°C, and the drying time is 6-24h. A coal-based porous graphene material is obtained;
[0045] S6: Mixing of ternary metal salts: mixing nickel salt, cobalt salt and manganese salt in any proportion to obtain a mixture;
[0046] The nickel salt, cobalt salt and manganese salt are corresponding sulfates, carbonates, chlorides, fluorides or hydroxides.
[0047] The mixing method is co-precipitation, liquid phase mixing or solid phase mixing.
[0048] S7: mixing the mixture with a lithium source: mixing the mixture with a lithium source to obtain a precursor material;
[0049] The lithium source is lithium carbonate, lithium hydroxide, lithium nitrate or lithium chloride.
[0050] The mixing method is liquid phase mixing or solid phase mixing.
[0051] S8: Sintering of precursor materials: placing the precursor materials in an atmosphere furnace (the atmosphere of the atmosphere furnace is high-purity oxygen or air or a mixed gas containing oxygen, and the volume flow rate of the atmosphere is 50 mL / min to 500 mL / min. The heating rate of the atmosphere furnace is 0.1°C / min to 20°C / min), the temperature is raised to a specified temperature (200°C to 1600°C) and kept warm for a period of time (0.5h to 24h), and then the atmosphere furnace is naturally cooled to room temperature to obtain a sintered mixed solid material;
[0052] S9: Cleaning and drying of the product: The mixed solid material after sintering is acid-washed and water-washed in turn. The cleaning method is vacuum filtration or solid-liquid separation by centrifuge. When the supernatant is neutral, the cleaned solid material is dried by vacuum drying, hot air drying or natural evaporation. The drying temperature is 60-160°C and the drying time is 6-24h. The ternary material is obtained;
[0053] The pickling solutions used in the pickling treatments of S5 and S9 are all dilute hydrochloric acid, dilute nitric acid or dilute acetic acid, and the concentrations of the pickling solutions are all 0.01 mol / L to 10 mol / L.
[0054] S10: Preparation of composite materials: Mixing coal-based porous graphene materials and ternary materials in a mass ratio of 1:100 to 100:1, using liquid phase mixing and solid phase mixing to obtain coal-based porous graphene composite ternary materials.
[0055] The present invention uses low-cost coal as raw material, fully mixes the activator with the coal powder, and adopts the process of carbonization followed by activation and subsequent cleaning and drying to prepare high-quality coal-based porous graphene materials with coordinated development of graphite microcrystals and developed pores. The pore grouping and microcrystalline structure of the porous graphene can be adjusted by changing the carbonization temperature, activation temperature, activator dosage, etc. The specific surface area of the obtained porous graphene can reach 2615m 2 g -1 , the total pore volume can reach 1.60cm 3 g -1 The pore size of the micropores is mainly distributed between 0.7 and 1 nm, and it contains a large number of mesopores and macropores, which provide sufficient space and fast transmission channels for the storage and diffusion of electrolyte ions.
[0056] Using nickel salt, cobalt salt and manganese salt as raw materials, high temperature solid phase method or coprecipitation method or sol-gel method or hydrothermal synthesis method or combustion method, etc., by changing the ratio of the three metal salt raw materials to prepare different types of ternary materials, the microcrystalline structure of the ternary materials is regulated to achieve bulk storage of ions. By mixing coal-based porous graphene and ternary materials in different proportions and different methods such as mechanical mixing, liquid phase mixing, low temperature sintering, etc., a hybrid capacitor positive electrode material of coal-based porous graphene composite ternary materials is obtained. When it is applied to the positive electrode material of lithium ion capacitors, and affected by the conditions such as the composite ratio and method, it is expected to achieve higher indicators. The present invention has broad application prospects in energy storage technology (such as hybrid capacitors) and other aspects.
[0057] Embodiment 1:
[0058] S1: Raw material refinement: 3 g of Zhundong coal is crushed, ground and sieved in sequence to obtain refined coal powder. The particle size of the refined coal powder is 120 mesh to 160 mesh.
[0059] S2: Carbonization of coal raw material: Place the refined coal powder in a high-purity nitrogen atmosphere furnace with an atmosphere volume flow rate of 200 mL / min and a heating rate of 5°C / min; the temperature is raised to a specified carbonization temperature of 700°C and maintained for 1 hour, and then the atmosphere furnace is naturally cooled to room temperature to obtain a carbonized solid substance.
[0060] S3: Mixing of activator and product: The carbonized solid material and the chemical activator potassium hydroxide in a mass ratio of 1:4 are fully mixed by liquid phase mixing to obtain a mixture.
[0061] S4: Activation of the mixture: The mixture was transferred to a nickel crucible and placed in a horizontal tubular high-purity nitrogen atmosphere furnace with an atmosphere volume flow rate of 200 mL / min; the heating rate of the atmosphere furnace was 5°C / min; the temperature was raised to the specified activation temperature of 1000°C and kept for 1 hour, and then the atmosphere furnace was naturally cooled to room temperature to obtain an activated mixed solid substance.
[0062] S5: Cleaning and drying of the activated product: The activated mixed solid material is sequentially acid-washed three times with dilute hydrochloric acid at a concentration of 5 mol / L, and washed with water until the supernatant is a neutral liquid with a pH of 7. The cleaning method is vacuum filtration; the cleaned solid material is vacuum dried at a drying temperature of 100° C. for 12 hours to obtain a coal-based porous graphene material.
[0063] S6: mixing ternary metal salts: mixing nickel hydroxide, cobalt hydroxide and manganese hydroxide in a mass ratio of 1:1:1 by solid phase mixing to obtain a mixture;
[0064] S7: mixing the mixture with a lithium source: mixing the mixture with lithium carbonate by solid phase mixing to obtain a precursor material.
[0065] S8: Sintering of precursor materials: Place the precursor materials in an atmosphere furnace with an air atmosphere and a volume flow rate of 100 mL / min; the heating rate of the atmosphere furnace is 5°C / min; the temperature is raised to a specified temperature of 800°C and kept for 2 hours, and then the atmosphere furnace is naturally cooled to room temperature to obtain a sintered mixed solid material.
[0066] S9: Cleaning and drying of the product: The mixed solid matter after sintering is acid-washed and washed with water in dilute hydrochloric acid with a concentration of 2 mol / L in turn until the supernatant is neutral. The cleaning method is vacuum filtration; the cleaned solid matter is dried by vacuum drying at a drying temperature of 100°C for 12 hours to obtain a ternary material.
[0067] S10: Mixing the coal-based porous graphene material and the ternary material in a mass ratio of 1:1 by solid phase mixing to obtain a coal-based porous graphene composite ternary material.
[0068] Experimental results:
[0069] like Figure 1 As shown, this is the SEM image of the coal-based porous graphene composite ternary material prepared in Example 1. It can be seen from the figure that after carbonization at 700°C and activation with potassium hydroxide at 1000°C for 1h, a "petal-like" texture appears on the surface of the carbon material, and the "petal-like" morphology is almost distributed throughout the entire carbon structure.
[0070] like Figure 2As shown, it is the Raman spectrum of the coal-based porous graphene composite ternary material prepared in Example 1, indicating that the carbon material has undergone a deep graphitization process.
[0071] like Figure 3 As shown, it is the electrochemical characteristic diagram of the coal-based porous graphene composite ternary material prepared in Example 1. The CV curves are all quasi-rectangular in shape, showing typical capacitive charge storage behavior.
[0072] Embodiment 2:
[0073] The difference between this embodiment and embodiment 1 is that:
[0074] S1: Take 5g Zhundong coal
[0075] S4: The temperature is raised to the designated activation temperature of 1000°C and kept at this temperature for 5 hours.
[0076] S5: drying temperature is 80°C;
[0077] S9: drying temperature is 80°C;
[0078] Experimental results:
[0079] like Figure 4 As shown, this is the SEM image of the coal-based porous graphene composite ternary material prepared in Example 2. It can be seen from the figure that after carbonization at 700°C and activation with potassium hydroxide at 1000°C for 5 hours, a "petal-like" texture appears on the surface of the material, which shows more significant fluctuations and deeper wrinkles than the texture of the material prepared in Example 1.
[0080] like Figure 5 As shown, it is the Raman spectrum of the coal-based porous graphene composite ternary material prepared in Example 2. Compared with the material prepared in Example 1, it has undergone deeper graphitization and has fewer defects.
[0081] like Figure 6 As shown in Figure 2, the electrochemical characteristics of the coal-based porous graphene composite ternary material organic supercapacitor prepared in Example 2, compared with the material prepared in Example 1, with the extension of activation time, the double-layer capacitance behavior is more obvious, which is related to the further improvement of the degree of graphitization. However, this enhancement of graphitization is accompanied by a significant decrease in specific capacitance, which is mainly caused by the loss of pore structure under high temperature and long-term treatment.
[0082] Embodiment 3:
[0083] The difference between this embodiment and embodiment 1 is that:
[0084] S4: The temperature is raised to the designated activation temperature of 900°C and kept at this temperature for 1 hour;
[0085] S5: Drying temperature is 80°C and drying time is 12h.
[0086] S9: Drying temperature is 80°C and drying time is 12h.
[0087] Experimental results:
[0088] like Figure 7 As shown, this is the SEM image of the coal-based porous graphene composite ternary material prepared in Example 3. It can be seen from the figure that after carbonization at 700°C and activation with potassium hydroxide at 900°C for 1h, a "petal-like" texture appears on the surface of the Zhundong coal, which is almost spread throughout the entire carbon structure.
[0089] like Figure 8 As shown, it is the TEM image of the coal-based porous graphene composite ternary material prepared in Example 3, in which obvious graphite ribbons appear.
[0090] like Fig. 9 The figure shows the comparison of nitrogen adsorption curve and pore size distribution curve of the coal-based porous graphene composite ternary material prepared in Examples 1 to 3. The material not only has a highly graphitized structure, but also exhibits a relatively high specific surface area and pore volume.
[0091] like Fig.10 As shown, the electrochemical characteristic diagram of the organic supercapacitor of the coal-based porous graphene composite ternary material prepared in Example 3, the CV curves all show a quasi-rectangular shape, showing typical capacitive charge storage behavior. More importantly, even when the scan rate is increased, the curve shape can still remain relatively regular, proving their excellent charge and discharge efficiency. The GCD curve also shows a considerable discharge time, reflecting a larger specific capacitance value. This is because the material has a developed pore and graphite lattice structure at the same time, and the optimization of this structure enables the electrode to more effectively store and conduct ions in the electrochemical reaction, thereby improving energy and power density.
[0092] like Fig.11 As shown, the cyclic voltammetry curve and constant current charge-discharge curve of the lithium ion capacitor with the coal-based porous graphene composite ternary material prepared in Example 3 as the positive electrode and the niobium-based oxide as the negative electrode are expected to achieve higher indicators under the influence of the composite ratio, method and other conditions, and by optimizing the kinetic matching ratio with the negative electrode material.
[0093] The surface adsorption storage of ions by porous graphene materials with high specific surface area made from coal activated by potassium-based activators, and the bulk storage of ions by ternary materials such as lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, or other ternary materials with nickel salt, cobalt salt, and manganese salt as raw materials and adjustable ratio of nickel, cobalt, and manganese, relate to a method for preparing a high-specific-energy hybrid capacitor positive electrode material that can achieve ion-surface coordinated storage. The present invention addresses the bottleneck that traditional surface adsorption storage positive electrode materials for hybrid capacitors are difficult to achieve high energy density storage, and adopts a method of composite coal-based porous graphene with ternary materials to achieve the preparation of high-specific-energy hybrid capacitor positive electrode materials that can have both ion bulk storage and surface storage.
[0094] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and range of equivalents of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
[0095] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a coal-based porous graphene composite ternary material, characterized in that: The method comprises the following steps: S1: Raw material refinement: The coal raw material is crushed, ground and screened in sequence to obtain refined coal powder; S2: Carbonization of coal raw materials: The refined coal powder is placed in an atmosphere furnace, the temperature is raised to a specified carbonization temperature and kept warm for a period of time, and then the atmosphere furnace is naturally cooled to room temperature to obtain a carbonized solid material; S3: Mixing the activator and the product: fully and evenly mixing the carbonized solid material and the chemical activator in a mass ratio of 1:0.1 to 10 to obtain a mixture; S4: Activation of the mixture: the mixture is transferred to a crucible and placed in an atmosphere furnace, the temperature is raised to a specified activation temperature and kept warm for a period of time, and then the atmosphere furnace is naturally cooled to room temperature to obtain an activated mixed solid material; S5: cleaning and drying of the activated product: the activated mixed solid material is sequentially acid-washed and water-washed until the supernatant is neutral, and then the cleaned solid material is dried to obtain a coal-based porous graphene material; S6: Mixing of ternary metal salts: mixing nickel salt, cobalt salt and manganese salt in any proportion to obtain a mixture; S7: mixing the mixture with a lithium source: mixing the mixture with a lithium source to obtain a precursor material; S8: sintering of precursor materials: placing the precursor materials in an atmosphere furnace, raising the temperature to a specified temperature and keeping the temperature for a period of time, then naturally cooling the atmosphere furnace to room temperature to obtain a sintered mixed solid material; S9: cleaning and drying of the product: the mixed solid material after sintering is sequentially acid-washed and water-washed until the supernatant is neutral, and the cleaned solid material is dried to obtain a ternary material; S10: Preparation of composite materials: Mixing the coal-based porous graphene material and the ternary material in a mass ratio of 1:100 to 100:1 to obtain a coal-based porous graphene composite ternary material.
2. The method for preparing a coal-based porous graphene composite ternary material according to claim 1, characterized in that: The particle size of the fine coal powder in S1 is 60 mesh to 200 mesh.
3. The method for preparing a coal-based porous graphene composite ternary material according to claim 1, characterized in that: S3 The chemical activator is one or more potassium-based activators.
4. The method for preparing a coal-based porous graphene composite ternary material according to claim 1, characterized in that: The pickling solutions used in the pickling treatments of S5 and S9 are all dilute hydrochloric acid, dilute nitric acid or dilute acetic acid, and the concentrations of the pickling solutions are all 0.01 mol / L to 10 mol / L.
5. The method for preparing a coal-based porous graphene composite ternary material according to claim 1, characterized in that: S6 The nickel salt, cobalt salt, and manganese salt are corresponding sulfates, carbonates, chlorides, fluorides, or hydroxides.
6. The method for preparing a coal-based porous graphene composite ternary material according to claim 1, characterized in that: S6 The mixing method is co-precipitation, liquid phase mixing or solid phase mixing.
7. The method for preparing a coal-based porous graphene composite ternary material according to claim 1, characterized in that: S7 The lithium source is lithium carbonate, lithium hydroxide, lithium nitrate or lithium chloride.
8. The method for preparing a coal-based porous graphene composite ternary material according to claim 1, characterized in that: The mixing method described in S7 is liquid phase mixing or solid phase mixing.
Citation Information
Patent Citations
Graphene-based composite ternary material, preparation method thereof, and lithium ion battery
CN103904330A
Preparation method for ternary positive electrode material of graphene composite lithium ion battery
CN104157854A
Ternary composite cathode material with three-dimensional network structure and preparation method of ternary composite cathode material
CN105702926A
Preparation method of nickel / manganese / lithium-graphene composite material for lithium ion batteries
CN107834054A
Method for preparing graphene using coal as raw material
CN107848805A
Cited By
Preparation method and application of titanium-niobium-oxygen in-situ doped porous carbon material
CN121493978A